Host Plant Resistance for Cowpea Insect Pest Management - Singh, S.R. (1987)
Insect pests are major constraints in cowpea production. Breeding for insect resistance is a major objective of cowpea improvement programme at IITA. Resistance to leafhoppers and aphids has been incorporated in advanced breeding lines thus eliminating the need for other control measures. Similarly, a moderate level of resistance to thrips and cowpea storage weevil has also been incorporated thus reducing the damage due to these two pests. A moderate level of resistance to legume pod-borer and pod sucking bugs has also been identified and is being incorporated in advanced breeding lines. The long term strategy is to develop cowpea cultivars with multiple resistance to insect and diseases with superior agronomic characters and local adaptability.